USE OF SOCIAL MEDIA IN FORMING THE RELIGIOUS CHARACTER OF TEENAGERS NURUL YAQIN MOSQUE, TUNJANG DUSUN, PAGUTAN VILLAGE, BATUKILIANG DISTRICT, REGENCY CENTRAL LOMBOK - muhamad ifan maulana (JOETAL: Journal of Education, Teaching and Learning, 2024)
This research aims to determine the use of Social Media, supporting and inhibiting factors in forming the religious character of teenagers at the Nurul Yaqin Mosque, Tunjang Hamlet, Pagutan Village, Batukliang District, Central Lombok Regency. The research method used qualitative with a descriptive approach. Data was collected through in-depth interviews, observation and analysis of Social Media content. The informants for this research are teenagers who actively use Social Media and are involved in religious activities at the local mosque. The research results show that the use of Social Media has a significant influence in shaping the religious character of teenagers, both positively and negatively. The use of social media expands teenagers' access to religious information, allowing them to participate in online religious discussions and activities, but also carries the risk of exposure to content that is inconsistent with religious values. Nevertheless, the Nurul Yaqin Mosque still plays an important role as a supporting institution in the process of forming the religious character of teenagers. Through religious programs, moral education and self-development, this mosque provides a platform for teenagers to actualize religious values ​​in everyday life. This research provides a deeper understanding of the relationship between the use of Social Media and the formation of teenagers' religious character, as well as its implications in the local community context. The practical implications of this research can be used as a basis for policy makers, educational institutions, and religious communities to develop more effective strategies in utilizing Social Media to support the formation of the religious character of teenagers.